The Role of Extracurricular Activity Management in Developing Speaking and Writing Skills - Afandi Afandi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2020)
It is not easy to speack arabic for a student who are not native speaker, but it will be solved through much rehearsal. The student are not native speaker will be easy to speak and write arabic. the rehearsal of this additional activity will be effective if it supports by right management. There are some purposes of this reasearch : 1. To know the planning of extracurricular for speaking and writing skill. 2. To know the organization of extracurricular for speaking and writing skill 3. To know the evaluation of extracurricular for speaking and writing skill. In This research, the researcher uses qualitative research approach and case study methode. there are two data sources of this reasearch namely primer and secondary data sources, collecting the data through interview, observation, and documentation. Whereas analysing the data uses mils and hubberman analysing models. Based on the result of this research, can take conclusion that management of addtional activity for speaking and writing skill, the first is planning, in this planning consist of establishing purpose, establishing programe, establishing advisor, establishing the fasility of the implamentation of speaking and writing skills. The second is organization, in this organization consist of distributing assigment and obligation to the teacher. The third is evalution, the evalution of extracurricular of speaking skill did orally whereas the evalution for writing skill through correcting the result of student’s wriring for one month.